Herd‐immunity across intangible borders: Public policy responses to COVID‐19 in Ireland and the UK. (26th November 2020) - Colfer, Barry
Abstract : The responses to COVID‐19 in Ireland and the UK differed, and will have consequences for life in these islands that will extend far beyond the current crisis. Ireland went into lockdown relatively early on 12 March, while after a slow initial response, with plans for herd immunity, the UK started introducing restrictions around 20 March and quickly became a world leader in cases. While the UK has also presented similar responses seen elsewhere in Europe, one further area of note sees the devolved responses in different parts of the UK diverge considerably. These differences cannot be explained purely in terms of epidemiological conditions, as the trajectories of the virus in England, Scotland, Wales, and Northern Ireland are broadly similar. The reality is that the leaders of the devolved governments reached different political judgments from PM Johnson, which may bring further pressure to bear on the UK's constitutional makeup.